2003
DOI: 10.2134/jeq2003.6300
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Oxidative Transformation of Chlorophenol Mixtures

Abstract: Chlorinated phenols are major industrial and agricultural xenobiotics that pollute soil and ground water. It has been shown that laccases catalyze the oxidative coupling of phenolic compounds. Therefore, the transformation of one or a mixture of several chlorinated phenols by a laccase from the fungus Trametes villosa was studied. Generally, if more than one phenol was added, the transformation of chlorinated phenols decreased, and if the concentration of the laccase was increased, the transformation of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 18 publications
0
29
1
2
Order By: Relevance
“…Phenols and chlorophenols are aromatic compounds of serious environmental concern because of their widespread use, toxicity for aquatic species, and occurrence throughout the environment (Katayama-Hirayama et al 1994;Reineke 1998;Bollag et al 2003). The chlorinated phenols are more toxic than the unsubstituted compound.…”
Section: Introductionmentioning
confidence: 99%
“…Phenols and chlorophenols are aromatic compounds of serious environmental concern because of their widespread use, toxicity for aquatic species, and occurrence throughout the environment (Katayama-Hirayama et al 1994;Reineke 1998;Bollag et al 2003). The chlorinated phenols are more toxic than the unsubstituted compound.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, wastewaters from industries such as polymeric resin production, oil refining and coking plants also contain chlorophenols (Bollag, Chu, Rao, & Gianfreda, 2003).…”
mentioning
confidence: 99%
“…Currently, many physical and chemical methods are available for decontaminating chlorinated phenols (Bollag, Chu, Rao, & Gianfreda, 2003). Many methods including sorption and biological degradation, chemical oxidation, and solvent extraction have been used for this purpose.…”
mentioning
confidence: 99%
“…Fungi have been described to degrade xenobiotics by cometabolism rather than using xenobiotics as sole carbon source (Bennett et al 2001). Several studies have demonstrated the ability of fungi to degrade 2,4-D and MCPA, and in most cases, lignin-degrading enzymes have been implicated (Bollag et al 2003;Sedarati et al 2003;Singleton 2001;Vroumsia et al 1999). Kalbitz et al (2003) found an enrichment of lignin-derived aromatic compounds in dissolved organic carbon (DOC) originating from biodegradation of maize straw and other plant residues.…”
Section: Mcpa-degrading Communitymentioning
confidence: 99%